The global financial crisis : how did we get here and how do we move forward - Odle, Maurice ([ILO-SRO] [Port of Spain]TT, 2009)
Deals with the significance of systemic weaknesses in the global financial system and financial sector weaknesses as a product of an extremist market philosophy. Focuses on the significance of the diminished role of the state and globalisation and the paradigm of free trade.